Identifying ‘Illat through Munasabah in Islamic Law: A Perspective of Imam Al-Ghazali - Hasballah, Khairuddin; Darna, Andi; Said, Wardana; Akbar, Hajarul; Karim Makinara, Ihdi; Fauzan, Faisal (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This study discusses the way in determining ‘illat through the munasabah method proposed by Imam al-Ghazali in the perspective of Islamic law. The study focuses on two main problems: the identification of ‘illat through munasabah and the legal formulation to utilize hikmat to obtain ‘illat according to al-Ghazali. This normative legal research used a legal history approach as an analytical tool to examine the Islamic scholars’ thoughts on concepts, theories and ways of doing istinbath. The study concluded that according to al-Ghazali there are three kinds of munasabah in determining ‘illat, consisting of munasib mu’atstsir, munasab mula’im, and munasib gharib. In munasib mu’atstsir, there is no issue found in seeking ‘illat because the ‘illat is understood directly from the nash or ijma’. Therefore, munasabah is no longer needed in the determining ‘illat. Here, the munasabah method focuses on munasib mula’im and munasib gharib in identifying ‘illat. Munasib mula’im seeks for the genus ‘illat, an ‘illat drawn from every event that has been predetermined by the nash, by examining the same hikmah in each of the events. Such hikmah is then used as the genus ‘illat which will later be applied as qiyas for other events that have been legally stipulated by the nash. On the other hand, munasib gharib seeks for the species ‘illat, an ‘illat obtained from an event that has been predetermined by the nash, with no comparison found in other events. ‘Illat determined from munasib gharib is also hikmah, having no concrete nature. In the perspective of legal history, this method of seeking ‘illat is inseparable from kalam and philosophy as was the development of the Islamic sciences at the time. As such, this had also affected al-Ghazali’s mastery in Islamic law as well as in other Islamic disciplines.